The impact of external stakeholders pressures on the intention to adopt environmental management practices and the moderating effects of firm size - Latip, Malisah; Sharkawi, Ismawati; Mohamed, Zainalabidin; Kasron, Norzalila (Small Business Institute, 2022)
SMEs in the food manufacturing sector represent a considerable proportion of mainstream businesses in Malaysia. The changes in the lifestyles of Malaysians have led to increased demand for convenience and processed foods, which has led to a growing number of food manufacturing establishments in Malaysia. Nevertheless, the expansion in the food manufacturing sector is followed by a rise in environmental issues. Therefore, to mitigate the impact of food manufacturing activities on the environment, one of the best possible solutions is to implement environmental management practices (EMPs). SMEs may encounter varying levels of pressure from customers, regulatory bodies, and the social community regarding environmental behavior and compliance. This study used the Stakeholder theory to develop the research model. The first objective of this study is to determine the effect of SMEs’ external stakeholders, including customer pressure, regulatory pressure, and social community pressure, on food manufacturing SMEs’ intention to adopt EMPs. The second objective is to test the effect of firm size as a moderating variable. A structured questionnaire was administered to 367 food manufacturing SMEs in Malaysia. The findings reveal that the SMEs’ intention to adopt EMPs was significantly related to customer, regulatory, and social community pressures. The study also discovered that firm size only moderated the relationship between customer pressure and the intention to adopt EMPs. The results provided a more robust understanding of the effect of external factors on SMEs’ intentions toward EMPs. Policymakers are recommended to carefully consider those factors to encourage more SMEs to adopt EMPs. SMEs should cultivate a learning and innovative culture to successfully embrace EMPs in a changing business environment.